2022
DOI: 10.1002/dmrr.3586
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic retinopathy in patients with newly diagnosed type 2 diabetes: A systematic review and meta‐analysis

Abstract: Aims: Type 2 diabetes mellitus (T2DM) can remain undiagnosed for many years, during which micro-and macro-vascular complications may develop. This study aimed to assess the worldwide prevalence of diabetic retinopathy (DR) in patients with newly diagnosed T2DM. Materials and Methods:We systematically searched electronic databases for relevant studies published from inception to 01 January 2022. Selected studies reported the prevalence of DR among patients with newly diagnosed T2DM, specifying the case definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 124 publications
1
11
0
1
Order By: Relevance
“…Its prevalence is projected to increase dramatically, marking an escalating public health concern ( 2 , 3 ). A prevalent microvascular complication of T2DM, diabetic retinopathy (DR), stands as a leading cause of blindness globally ( 4 , 5 ). In China, the prevalence of DR among diabetic individuals exhibits considerable variation, with estimates ranging from 18.45% to 31.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence is projected to increase dramatically, marking an escalating public health concern ( 2 , 3 ). A prevalent microvascular complication of T2DM, diabetic retinopathy (DR), stands as a leading cause of blindness globally ( 4 , 5 ). In China, the prevalence of DR among diabetic individuals exhibits considerable variation, with estimates ranging from 18.45% to 31.8%.…”
Section: Introductionmentioning
confidence: 99%
“…As the prevalence of diabetes increases and the lifespan of patients extends, diabetic retinopathy (DR) and its associated visual impairments are also rapidly increasing worldwide 2 4 . DR is the most common microvascular complication of T2DM and is recognized as a leading cause of blindness and visual impairment in the working-age population globally 3 , 5 . Although numerous studies have focused on the pathogenesis and influencing factors of DR, including epigenetic mechanisms such as DNA methylation, histone modifications, as well as miRNAs and long non-coding RNA (lnc-RNA) regulation 6 8 , the exploration of the relationship between serum albumin (ALB) and DR remains inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic retinopathy (DR), a common and severe complication of diabetes, leads to vision impairment and ocular morbidity in roughly 200 million patients globally [ 1 ]. Our group and others have shown that metabolic disease, partly due to the release of lipopolysaccharide (LPS), which induces low-grade systemic inflammation, influenced the severity of diabetes, [ 2 5 ] and exacerbated retinal damage in experimental DR [ 4 ].…”
Section: Introductionmentioning
confidence: 99%